The impact of consumer reviews and ratings on purchase decisions on the Tokopedia marketplace in Indonesia - Hidayansyah, Robi; Ahmad, Aripin; Nabila, Nuzul Inas (FEB - Universitas Lampung, 2023)
The rapid development of technology has caused a shift in consumer shopping behavior from offline to online around the world including in Indonesia, one of which is marked by the growth of e-commerce which has increased significantly. E-commerce Tokopedia is one of the largest e-commerce in Indonesia which provides a variety of features that are a source of information for consumers in determining the products that consumers will buy, one feature that is quite important is consumer reviews and ratings. The purpose of this study was to determine the effect of the variables of consumer reviews and ratings as independent variables on purchasing decisions as the dependent variable on the Tokopedia marketplace in Indonesia. This study used a survey method by distributing questionnaires to 130 respondents. The sample was taken using the purposive sampling technique, which is a sampling technique with criteria according to the researcher's determination. The analytical method used in this research is Multiple Linear Regression Analysis. The results showed that the variables of consumer reviews and judgments had a suggestive effect on the purchasing decision variable.